Perception and audience motivation to read literature section in the print / Muhammad Aniq Azlan and Mohd Syuhaidi Abu Bakar - Azlan, Muhammad Aniq; Abu Bakar, Mohd Syuhaidi (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
Literature is a creative work with high aesthetic value. Understanding literature requires frequent and deep reading because generally the best literary work has layered messages with various meanings to be interpreted. However, nowadays there are some assumptions that the literary work is in a state of decline due to several issues. Besides this, the level of literature reading is also deteriorating. This study focuses to understand audience perceptions and motivation to indulge in literature pieces in the print. It used a qualitative method of interviewing 14 informants. The results of this study found that audience perceived that people no longer read literary works as the print has cut down the pucblication of such material. This study also found that audience were highly motivated to read the literature in print.